1978
DOI: 10.1161/01.str.9.5.484
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous glycerol in cerebral infarction: a controlled 4-month trial.

Abstract: SUMMARY A double-blind, randomized trial was performed with 51 patients suffering from focal ischemic lesions in the territory of the middle cerebral artery. Intravenous infusions of 10% glycerol in 0.9% NaCI -5% glucose solutions were administered twice daily for 6 days to 26 patients, and the same amount of NaCI -glucose solutions to 25 controls. Glycerol did not reduce mortality (9 deaths in each group). The functional recovery was assessed by repeated neurological examinations during the 4 month trial. Gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…In another steroid trial, Norris 22 introduced the idea of weighing modalities in a system of nearly 300 points. Fawer 23 in 1978 used a similar system to evaluate the effects of glycerol in cerebral infarction. Here again, the use of such systems for monitoring is limited by their complexity and the length of time needed to evaluate patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another steroid trial, Norris 22 introduced the idea of weighing modalities in a system of nearly 300 points. Fawer 23 in 1978 used a similar system to evaluate the effects of glycerol in cerebral infarction. Here again, the use of such systems for monitoring is limited by their complexity and the length of time needed to evaluate patients.…”
Section: Discussionmentioning
confidence: 99%
“…A consequence of this might be a loss of sensitivity but our goal is not to duplicate the neurological examination but rather to detect clinically noteworthy differences in neurological status, c) be relevant for modalities which are most commonly affected in acute stroke, d) be easy to use and interpret by observers with different medical training, e) be brief, f) be practical and simple. Patients who are stuporous or comatose should be evaluated with the Glasgow Coma Scale 12 which has previously been shown to be reliable 23 and is also widely used by the neurological and neurosurgical community. 26 Although presently used in certain centers to follow stroke patients, the Glasgow Coma Scale is felt to be too insensitive in most of those cases especially if the patient's level of consciousness is not impaired.…”
Section: Scoring Systemmentioning
confidence: 99%
“…With the large doses of steroids which have been used, infective complications and elevation of plasma glucose or exacerbation of diabetes are frequent (Poungvarin et al, 1987). Despite many studies with intravenous glycerol there is no consensus on its effect on stroke (Bayer et al, 1987;Fawer et al, 1978;Frei et al, 1987;Gilsanz et al, 1975;Larsson et al, 1976;Mathew et al, 1972;Meyer et al, 1975). In an overview of the published trials, Sandercock (1987) concluded that the 6 week mortality in stroke patients after glycerol may fall by 36% compared with placebo, but that the 95% confidence limits for this improvement range from 4%-58%.…”
Section: Anti-oedema and Other Agentsmentioning
confidence: 99%
“…No uniform scale of the severity of the strokes was used in the trials which excluded this outcome mea sure from analysis. One of the trials [8] presented the final outcome after 4 months only and was therefore excluded.…”
Section: Methodsmentioning
confidence: 99%